2015
DOI: 10.1057/mel.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal investment strategy in a container terminal: A game theoretic approach

Abstract: A b s t r a c t This article investigates the optimal strategy for potential investments that may be adopted by port authorities to attract more carriers. A mathematical model is formulated to represent the main criteria used by carriers to evaluate a specific port. Then, a game theory approach is used to model the competition between several port authorities to attract carriers via maximizing their utility functions. The game type suggested is Sealed-Bid with one round. The results indicate that the optimal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Investigating optimal investment strategy in a CT, Kaysi and Nehme 18 argued that the optimal investment strategy implemented by a port depends on the port’s location, resource availability, objective profitability, and other ports’ reactions to investment. Based on the result, the authors suggested cooperation among the different terminal companies in sharing information to minimize investment cost and competition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigating optimal investment strategy in a CT, Kaysi and Nehme 18 argued that the optimal investment strategy implemented by a port depends on the port’s location, resource availability, objective profitability, and other ports’ reactions to investment. Based on the result, the authors suggested cooperation among the different terminal companies in sharing information to minimize investment cost and competition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By solving a game of four players consisting of two ports and two liners, they found that ports have higher power than liners in imposing high service charges. Kaysi and Nehme (2016) found that the optimal investment strategy of several ports competing with each other to attract carriers depends on the port's (i) present status compared to the competing ones, (ii) availability of resources, (iii) expected profitability and (iv) competitors' reactions to the investment. In that study, the suggested game is Bidding/Auction via Sealed-Bid or First-Price Auction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They considered an investment in the port capacity as a dynamic game and concluded that the longer the interval between each investment, the higher the port charges are. Indeed, at a strategic level, the optimal investment strategy for a port may be unique and largely dependent on factors such as its resource availability, expectation, current position, and competitors' reactions (Kaysi and Nehme, 2016).…”
Section: Game Theorymentioning
confidence: 99%